Lung cancer diagnosed in the young is associated with enrichment for targetable genomic alterations and poor prognosis - Sacher, Adrian G. (JAMA Oncol, 2016)
IMPORTANCE: NSCLC in the young is a rare entity and the genomics and clinical characteristics of this disease are poorly understood. In contrast, young age at diagnosis has been demonstrated to define unique disease biology in other cancers. Here we report on the association of young age with targetable genomic alterations and prognosis in a large cohort of NSCLC patients. OBJECTIVE: To determine the relationship between young age at diagnosis and both the presence of a potentially targetable genomic alteration as well as prognosis and natural history. DESIGN: All patients with NSCLC genotyped at the Dana-Farber Cancer Institute between 2002–2014 were identified. Tumor genotype, patient characteristics and clinical outcomes were collected. Multivariate logistic regression was used to analyze the relationship between age and mutation status. Multivariate Cox proportional hazard models were fitted for survival analysis. SETTING: A National Cancer Institute (NCI) designated comprehensive cancer center. PARTICIPANTS: All patients with NSCLC seen at the Dana-Farber Cancer Institute between 2002–2014 who underwent tumor genotyping. MAIN OUTCOME MEASURE: The frequency of targetable genomic alterations by defined age categories as well as the association of these age groups with survival. RESULTS: 2237 patients with NSCLC were studied. EGFR (p=0.02) and ALK (P<0.01) were associated with younger age, and a similar trend existed for HER2 (p=0.15) and ROS1 (p=0.1) but not BRAF V600E (p=0.43). Amongst patients tested for all 5 targetable genomic alterations, younger age was associated with an increased frequency of a targetable genotype (p<0.01). Those diagnosed at age 50 or younger have a 59% increased likelihood of harboring a targetable genotype. While presence of a potentially targetable genomic alteration treated with a targeted agent was associated with improved survival, the youngest and oldest age groupings had similarly poor outcomes even when a targetable genotype was present. CONCLUSION & RELEVANCE: Younger age is associated with an increased likelihood of harboring a targetable genotype and is an underappreciated clinical biomarker in NSCLC. The survival of young NSCLC patients is unexpectedly poor compared to other age groups, suggesting more aggressive disease biology. These findings underscore the importance of comprehensive genotyping including NGS in younger patients with lung cancer.